2022
DOI: 10.3390/brainsci12030392
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Behavioral and Objective Measures of Sound Intensity in Normal-Hearing Listeners and Hearing-Aid Users: A Pilot Study

Abstract: Background: For hearing-impaired individuals, hearing aids are clinically fit according to subjective measures of threshold and loudness. The goal of this study was to evaluate objective measures of loudness perception that might benefit hearing aid fitting. Method: Seventeen adult hearing aid users and 17 normal-hearing adults participated in the study. Outcome measures including categorical loudness scaling, cortical auditory evoked potentials (CAEPs), and pupillometry. Stimuli were 1-kHz tone bursts present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 74 publications
0
4
0
Order By: Relevance
“…Another possibility is that increased loudness due to binaural summation contributed to greater pupil dilation in the Bilateral condition compared to either monaural condition. Indeed, Legris et al (2022) demonstrated increasing maximum pupil diameter with increasing tone burst level (40 dBA, 60 dBA, 80 dBA) in both NH participants and hearing aid users. For NH participants, pupil dilation was significantly larger for all increases in level, but for hearing aid users, pupil dilation was only significantly different when comparing the 40 dBA condition to 80 dBA condition, regardless of whether or not participants were using their hearing aids.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Another possibility is that increased loudness due to binaural summation contributed to greater pupil dilation in the Bilateral condition compared to either monaural condition. Indeed, Legris et al (2022) demonstrated increasing maximum pupil diameter with increasing tone burst level (40 dBA, 60 dBA, 80 dBA) in both NH participants and hearing aid users. For NH participants, pupil dilation was significantly larger for all increases in level, but for hearing aid users, pupil dilation was only significantly different when comparing the 40 dBA condition to 80 dBA condition, regardless of whether or not participants were using their hearing aids.…”
Section: Discussionmentioning
confidence: 91%
“…For NH participants, pupil dilation was significantly larger for all increases in level, but for hearing aid users, pupil dilation was only significantly different when comparing the 40 dBA condition to 80 dBA condition, regardless of whether or not participants were using their hearing aids. The 20 dB step size used by Legris et al (2022) corresponds to a fourfold increase in loudness, whereas an increase of about 3 dB, as is typical for binaural summation, only corresponds to a 1.2-fold increase in loudness ( Epstein and Florentine, 2012 ). Thus, the need to use large step sizes, especially in the hearing aid user group, indicates that the potential 3 dB of binaural summation experienced by BiCI users in the present study is very unlikely to have caused any significant change in pupil dilation.…”
Section: Discussionmentioning
confidence: 99%
“…To investigate the correlation among oxidative stress responses, elemental content, and metabolomics data, an explorative method called "focused PCA" was performed (Falissard 1999). This method is advantageous when the relationship between a responsive variable (the focused one) and explanatory variables is sought (Nicoletto et al 2018;Mander et al 2021;Hequet et al 2022;Legris et al 2022).…”
Section: Explorative Analysis By Focused Pcamentioning
confidence: 99%
“…Pupil also reacts to pure tones (Legris et al, 2022) but also to emotional sounds such as vocalizations or voices that also induced dilation (Cherng et al, 2020;Zekveld et al, 2018), that is modulated, as for visual stimuli, by authenticity (Cosme et al, 2021). Strong auditory emotions through vocalizations, whether positive (baby laughing) or negative (a couple fighting), induce pupil dilation (Jin et al, 2015;Partala & Surakka, 2003), with a larger effect for negative compared to positive stimuli (Babiker et al, 2015).…”
Section: Introductionmentioning
confidence: 99%